In silico genome analysis reveals the metabolic versatility and biotechnology potential of a halotorelant phthalic acid esters degrading Gordonia alkanivorans strain YC-RL2 - Ruth Nahurira; Junhuan Wang; Yanchun Yan; Yang Jia; Shuanghu Fan; Ibatsam Khokhar; Adel Eltoukhy (AMB Express, 2019)
Abstract Members of genus Gordonia are known to degrade various xenobitics and produce secondary metabolites. The genome of a halotorelant phthalic acid ester (PAEs) degrading actinobacterium Gordonia alkanivorans strain YC-RL2 was sequenced using Biosciences RS II platform and Single Molecular Real-Time (SMRT) technology. The reads were assembled de novo by hierarchical genome assembly process (HGAP) algorithm version 2. Genes were annotated by NCBI Prokaryotic Genome Annotation Pipeline. The generated genome sequence was 4,979,656 bp with an average G+C content of 67.45%. Calculation of ANI confirmed previous classification that strain YC-RL2 is G. alkanivorans. The sequences were searched against KEGG and COG databases; 3132 CDSs were assigned to COG families and 1808 CDSs were predicted to be involved in 111 pathways. 95 of the KEGG annotated genes were predicted to be involved in the degradation of xenobiotics. A phthalate degradation operon could not be identified in the genome indicating that strain YC-RL2 possesses a novel way of phthalate degradation. A total of 203 and 22 CDSs were annotated as esterase/hydrolase and dioxygenase genes respectively. A total of 53 biosynthetic gene clusters (BGCs) were predicted by antiSMASH (antibiotics & Secondary Metabolite Analysis Shell) bacterial version 4.0. The genome also contained putative genes for heavy metal metabolism. The strain could tolerate 1 mM of Cd2+, Co2+, Cu2+, Ni2+, Zn2+, Mn2+ and Pb2+ ions. These results show that strain YC-RL2 has a great potential to degrade various xenobiotics in different environments and will provide a rich genetic resource for further biotechnological and remediation studies.